Indian foreign policy in a unipolar world - Pant, Harsh V. (New Delhi : Routledgw, 2013)
" India's foreign policy, out of the structural confines of the Cold War strategic framework, has become more expansive in defining its priorities over the last few years. With the rise of its economic and military capabilities and strategic interests, India has shaped a diplomacy that is much more aggressive in the pursuit of those interests. Tracing the trajectory of India's foreign policy in the 21st century, this book examines the factors that have shaped the Indian response towards this emerging international security environment. Including a new Afterword, this updated volume looks at the major influences that have shaped India's foreign policy in recent years, in the context of its engagements with strategically important regions across the globe, and its relations with major global powers. The volume will prove invaluable to those studying politics and international relations, diplomatic and political history, defence and military studies, and South Asian studies."--Back cover.
Introduction / Harsh V. Pant. -- Part I. Major Themes in Indian Foreign Policy. India and the Global Balance of Power: A Neorealist Snapshot / Devin T. Hagerty ; India and the Emerging Non-Proliferation Order: The Second Nuclear Age / C. Raja Mohan ; India and the Challenge of Global Terrorism: The 'Long War' and Competing Domestic Visions / Timothy D. Hoyt ; India and Energy Security: A Foreign Policy Priority / Manjeet S. Pardesi and Sumit Ganguly. -- Part II. India and Major Global Powers. India and the US: Embracing a New Paradigm / C. Christine Fair ; India and China: As China Rises, India Stirs / Mohan Malik ; India and Russia: Renewing the Relationship / Deepa M. Ollapally ; India and the EU: A Long Road Ahead / Fraser Cameron. -- Part III. India's Regional Policy. India and South Asia: Towards a Benign Hegemony / Stephen F. Burgess ; India and the Middle East: A Re-Assessment of Priorities? / Harsh V. Pant ; India and Central Asia: Part of the New Great Game / Stephen Blank ; India and East Asia: A Region 'Rediscovered' / Manish Dabhade ; Afterword / Harsh V. Pant.
"With a new afterword"--Front cover.
Includes bibliographical references (pages [336]-370) and index.
Keywords: India -- Foreign relations -- 21st century; India -- Foreign relations -- United States; India -- Foreign relations -- Russia (Federation); India -- Foreign relations -- China